Relationship between air pollution exposure and the progression of idiopathic pulmonary fibrosis in Madrid: Chronic respiratory failure, hospitalizations, and mortality. A retrospective study - Mariscal-Aguilar, Pablo; Gómez-Carrera, Luis; Carpio, Carlos; Zamarrón, Ester; Bonilla, Gema; Fernández-Velilla, María; Torres, Isabel; Esteban, Isabel; Regojo, Rita; Díaz-Almirón, Mariana; Gayá, Francisco; Villamañán, Elena; et al. (Frontiers in Public Health, 2023)
Introduction Air pollution has a significant impact on the morbidity and mortality of various respiratory diseases. However, this has not been widely studied in diffuse interstitial lung diseases, specifically in idiopathic pulmonary fibrosis. Objective In this study we aimed to assess the relationship between four major air pollutants individually [carbon monoxide (CO), nitrogen dioxide (NO2), ozone (O3), and nitrogen oxides (NOx)] and the development of chronic respiratory failure, hospitalization due to respiratory causes and mortality in patients with idiopathic pulmonary fibrosis. Methods We conducted an exploratory retrospective panel study from 2011 to 2020 in 69 patients with idiopathic pulmonary fibrosis from the pulmonary medicine department of a tertiary hospital. Based on their geocoded residential address, levels of each pollutant were estimated 1, 3, 6, 12, and 36 months prior to each event (chronic respiratory failure, hospital admission and mortality). Data was collected from the air quality monitoring stations of the Community of Madrid located <3.5 km (2.2 miles) from each patient's home. Results The increase in average values of CO [OR 1.62 (1.11–2.36) and OR 1.84 (1.1–3.06)], NO2 [OR 1.64 (1.01–2.66)], and NOx [OR 1.11 (1–1.23) and OR 1.19 (1.03–1.38)] were significantly associated with the probability of developing chronic respiratory failure in different periods. In addition, the averages of NO2, O3, and NOx were significantly associated with the probability of hospital admissions due to respiratory causes and mortality in these patients. Conclusion Air pollution is associated with an increase in the probability of developing chronic respiratory failure, hospitalization due to respiratory causes and mortality in patients with idiopathic pulmonary fibrosis.